Efficiency of CFC taxation concerning hybrid instruments – a comparative analysis of Spain, Germany, and Austria - Thomas Kollruss (Cogent Business & Management)
The objective of this study is to show that an indirect interest in a controlled foreign corporation (CFC) through hybrid participation instruments may not be subject to CFC taxation. This is the case where the taxpayer holds a hybrid participation instrument in a foreign intermediary company (equity-like profit participation rights) and the intermediary company holds an interest in the share capital of the CFC. In such an ownership structure, the CFC rules of some countries have a structural weakness. This issue has not yet been examined in the literature. Methodologically, the research questions are pursued with a theoretical and legal analysis. This study is groundbreaking because it is the first to analyse the effectiveness of CFC legislation, which was introduced for the first time in all 27 EU Member States in 2019 as a result of the OECD’s BEPS initiative (ATAD), in the case of hybrid participation instruments. It breaks new ground in focusing on the interaction of hybrids with CFC rules. This study not only identifies the deficiencies of the current CFC legislation but also develops a concrete reform of the laws to close these gaps. The results of the study on strengthening the taxation of CFCs make a significant contribution to curbing international profit shifting.